The Relationship between Emotional Intelligence and Stress in Students Experiencing a Quarterlife Crisis at the Faculty of Psychology, Medan Area University - Franyanti, Alvira; Sisca Wardani, Rachma; Rahmi Syafitri, Sheila (Lafadz Jaya Publisher, 2024)
This research aims to look at the relationship between emotional intelligence and stress in students experiencing a quarterlife crisis. The hypothesis proposed is that there is a negative relationship between emotional intelligence and stress. The population in this study was 489 psychology students at Medan Area University and the sample obtained from the screening test was 43 students. The method in this research uses quantitative methods. Distribution of the emotional intelligence scale with stress using a Likert scale. The data analysis method used in this research is Product Moment Correlation. Based on the calculation of r Product Moment analysis with coefficient value (rxy) = -0.579 and coefficient (r2) = 0.336 with p= 0.000 < 0.05. These results show that the hypothesis proposed in this research is accepted, namely that there is a negative relationship between emotional intelligence and stress. This means that the lower the emotional intelligence, the higher the stress. Another result obtained from this research is that emotional intelligence at the Faculty of Psychology, Medan Area University is indicated to be low with an average empirical value obtained of 86.35, while stress is indicated to be high with an empirical value obtained of 129.16.